KESIAPAN FASILITAS WATER SANITATION HYGIENE (WASH) DAN PENERAPAN PROTOKOL KESEHATAN TENAGA PENGAJAR PADA MASA PANDEMI COVID-19 DI SEKOLAH DASAR NEGERI KOTA PALEMBANG - Yustini Ardillah; Dwi Septiawati; Yuanita Windusari (JURNAL EKOLOGI KESEHATAN, 2021)
ABSTRACT During the COVID-19 pandemic, social restrictions were imposed in Indonesia, thus making all activities recommended from home, including teaching and learning activities in schools. But in some areas face-to-face learning has begun to be disseminated, so it is necessary to conduct a review to determine school readiness including sanitation facilities, and implementation of health protocols. Sampling was done by simple random sampling consisting of 326 teachers from 56 elementary schools in 10 sub-districts in the city of Palembang. data analysis was univariate, namely maintaining distance, washing hands with soap, and using masks, while the variables for sanitation facilities are facilities for washing hands with soap, waste disposal facilities, waste water disposal facilities, clean water, and toilets. It was found that 38.4% of teachers have not been disciplined in washing their hands with soap, 20.7% have not kept their distance in their activities and 47.2% have not been disciplined in using masks. As many as 55.4% of schools do not have adequate hand washing facilities with soap, around 80% of facilities for garbage disposal and water disposal are not standardized. As many as 21.4% of schools that do not have access to clean water according to standards, and the cleanliness of toilets that are not clean is 37.5%. School readiness must be worth 100% of all aspects to ensure the prevention of the transmission of the COVID-19 virus. The provision of sanitation facilities needs to be carried out by schools to the maximum, so that local government support is needed. Keywords: Sanitation, health protocols, primary school, COVID-19 ABSTRAK Pada masa pandemi COVID-19 pembatasan sosial diberlakukan di Indonesia, sehingga membuat semua kegiatan dianjurkan dari rumah, termasuk kegiatan belajar mengajar di sekolah. Namun di beberapa wilayah mulai disosialisasikan pembelajaran secara tatap muka, sehingga perlu dilakukan peninjauan untuk mengetahui kesiapan sekolah meliputi fasilitas sanitasi dan penerapan protokol kesehatan. Penarikan sampel dilakukan secara simple random sampling terdiri dari 326 guru dari 56 SD di 10 kecamatan di Kota Palembang. Analisis data secara univariat yaitu menjaga jarak, mencuci tangan menggunakan sabun, dan menggunakan masker, sedangkan variabel fasilitas sanitasi adalah sarana cuci tangan dengan sabun, sarana tempat pembuangan sampah, sarana pembuangan air limbah, air bersih, dan toilet. Ditemukan sebanyak 38,4% guru belum disiplin mencuci tangan dengan sabun, 20,7% belum menjaga jarak dalam beraktivitas, dan 47,2% belum disiplin dalam menggunakan masker. Sebanyak 55,4% sekolah belum memiliki sarana cuci tangan pakai sabun yang memadai, sarana tempat pembuangan sampah dan pembuangan air yang belum standar sekitar 80%. Sebanyak 21,4% sekolah yang belum memiliki akses air bersih sesuai standar dan kebersihan toilet yang belum bersih sebesar 37,5%. Kesiapan sekolah harus bernilai 100% dari semua aspek untuk menjamin pencegahan penularan virus COVID-19. Penyediaan fasilitas sanitasi perlu dilakukan sekolah secara maksimal, sehingga diperlukan dukungan pemerintah setempat. Kata kunci: Sanitasi, protokol kesehatan, sekolah dasar, COVID-19